2007
DOI: 10.1071/wr06084
|View full text |Cite
|
Sign up to set email alerts
|

Bait consumption by, and 1080-based control of, feral pigs in the Mediterranean climatic region of south-western Australia

Abstract: The consumption of five non-toxic, grain-based baits, and the effectiveness of the preferred baits when treated with 1080 in reducing pig numbers, were determined for feral pigs (Sus scrofa) in several areas in the Mediterranean agricultural region of Western Australia. Fermented wheat with added blood and bone proved an effective attractant for feral pigs, and for determining areas of pig activity. Wheat and malted barley were the preferred baits, there was a variable response to lupins, and commercial pig pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
(64 reference statements)
0
6
0
Order By: Relevance
“…This research was subsequently augmented by studies on free-ranging feral swine, including bait uptake and consumption studies (McIlroy et al, 1993;Choquenot and Lukins, 1996), compound 1080 intake , risk assessments to non-target animals (McIlroy, 1992;Twigg et al, 2005a), the effectiveness of ground baiting campaigns with compound 1080 (Hone and Pedersen, 1980;Hone, 1983;Twigg et al, 2005b;Cowled et al, 2006a;Twigg et al, 2006Twigg et al, , 2007 and warfarin McIlroy and Saillard, 1989;Saunders et al, 1990;Choquenot et al, 1990), and the effectiveness of aerial baiting campaigns (Mitchell, 1998;Fleming et al, 2000). Compound 1080 and warfarin have also been used to eradicate feral swine from Santiago Island in the Galá pagos archipelago, Ecuador (Coblentz and Baber, 1987;Cruz et al, 2005).…”
Section: Toxicantsmentioning
confidence: 99%
“…This research was subsequently augmented by studies on free-ranging feral swine, including bait uptake and consumption studies (McIlroy et al, 1993;Choquenot and Lukins, 1996), compound 1080 intake , risk assessments to non-target animals (McIlroy, 1992;Twigg et al, 2005a), the effectiveness of ground baiting campaigns with compound 1080 (Hone and Pedersen, 1980;Hone, 1983;Twigg et al, 2005b;Cowled et al, 2006a;Twigg et al, 2006Twigg et al, , 2007 and warfarin McIlroy and Saillard, 1989;Saunders et al, 1990;Choquenot et al, 1990), and the effectiveness of aerial baiting campaigns (Mitchell, 1998;Fleming et al, 2000). Compound 1080 and warfarin have also been used to eradicate feral swine from Santiago Island in the Galá pagos archipelago, Ecuador (Coblentz and Baber, 1987;Cruz et al, 2005).…”
Section: Toxicantsmentioning
confidence: 99%
“…One study found that the maximum distance between points visited on a given day was, on average, 0.4 miles for sounders and 0.7 miles for boars. These extremes in daily position depended on the availability of food and water (Kavanaugh and Linhart 2000;Twigg et al 2007). Despite ample data regarding habitat preferences and range, specific daily movements of feral pigs are difficult to predict.…”
Section: Habitat Range and Travelmentioning
confidence: 99%
“…In Spain, the use of lethal means other than shooting to control wild boar damage and diseases is not allowed. Along with hunting, livetrapping and habitat management, both wild boar and feral-pig control has been carried out with baits containing either poison (McIlroy et al 1989;Saunders et al 1990;Cowled et al 2006;Twigg et al 2007) or contraceptives (Linhart et al 1997).…”
Section: Introductionmentioning
confidence: 99%